Pathophysiology of Hyperechogenic Bowel in Congenitally Human Cytomegalovirus Infected Fetuses - Liliana Gabrielli; Maria P. Bonasoni; Angela Chiereghin; Giulia Piccirilli; Eva C. Borgatti; Giuliana Simonazzi; Nunzio C. M. Salfi; Ione Tamagnini; Tiziana Lazzarotto (Microorganisms, 2020)
Hyperechogenic bowel (HB) is a nonspecific ultrasound finding that can be associated with human cytomegalovirus (CMV) congenital infection. In this study, we investigated HB pathophysiology in CMV-infected fetuses. We examined small and large intestine as well as pancreas in 8 fetuses at 22 weeks of gestation with congenital CMV infection. Ultrasound findings showed 4 fetuses with HB and 4 without. As negative group, 4 fetuses without CMV infection and without HB were studied. Immunohistochemistry for CMV, lymphocytic infiltrate, B-cell leukemia/lymphoma-2 (bcl-2), CD-117, cystic fibrosis transmembrane regulator (CFTR) were performed. HB fetuses showed multiple and sequential CMV-positive ganglion cells of Auerbach’s myenteric plexus. In the ganglia, bcl-2 was weakly expressed representing a reduced neuronal functionality. CD-117 revealed a regular distribution of Cajal cells, the pacemakers of intestinal contractility. Pancreas showed normal CFTR staining, indicating a preserved exocrine secretion, thus unlikely a contributory factor in HB. In CMV-infected fetuses without HB, CMV-positive cells were scatteredly found in ganglion cells and bcl-2 was strongly expressed. Intestinal CD-117 and pancreatic CFTR expression were similar to fetuses with HB. In conclusion, fetal CMV infection of the bowel may lead to peristalsis impairment (paralytic ileus) due to intestinal plexus involvement, which at ultrasound appeared as HB.